Effect of Indirect and Direct Boiling on the Physico-chemical Properties of Camel Milk - Mohammed, Sabah, A. A.; El Zubeir, Ibtisam, E. M. (Journal of Veterinary Medicine and Animal Production, 2021)
This study was carried out to evaluate the effect of boiling on the physicochemical properties of camel milk (total solids, fat, protein, casein, whey protein, lactose, ash, vitamin C, density and acidity). Five batches of camel milk samples were collected during the period from June to September 2014. Camel milk samples in each batch were divided into 3 equal portions. The first portion was raw milk (control), the second portion was subjected to indirect boiling and the third portion was subjected to direct boiling. The results indicated that the mean values of the total solids, fat, total proteins, casein, whey protein, lactose, ash, density, acidity and vitamin C for raw camel milk were 11.63±0.61%, 3.67±0.36%, 3.12±0.20%, 2.04±0.15%, 0.77±0.04%, 4.19±0.13%, 0.63±0.04%, 1.026±1.04 gm/cm3, 0.17 ±0.01% and 23.70±0.20 mg/l, respectively. Boiling had no significant (P>0.05) effect on fat, total protein and acidity. However significant (P<0.05) differences were found between the milk samples that were subjected to direct boiling and raw milk in total solids and lactose (13.44±0.34% and 4.77± 0.11%, respectively). The mean values of camel milk that was subjected to indirect boiling revealed 12.62 ±0.51% and 4.52±0.14% for total solids and lactose, respectively. There were also significant (P<0.01) differences between boiled camel milk and raw camel milk samples in ash, density, casein, whey protein and vitamin C content (0.81±0.04%, 1.032±0.61gm/cm3, 2.98±0.12%, 0.32±0.03%, 9.11±0.30 mg/l respectively), for camel milk samples subjected to direct boiling. However the mean values for camel milk subjected to indirect boiling were 2.56±0.14% for casein, 0.48±0.03% for whey protein and 16.83±0.59 mg/l for vitamin C. Hence this study indicated that boiling treatment reduced the content of whey proteins and vitamin C of camel milk. However indirect boiling could represent a good alternative procedure to direct boiling.